Analisis Bibliometrik: Fokus Penelitian Metode Scaffolding terhadap Kemampuan Computational Thinking (2016-2022) - Nurhaliza, Nurhaliza; Astuti, Astuti; Zulfah, Zulfah; Ediputra, Kasman (Universitas Teknokrat Indonesia, 2024)
The aim of this bibliometric analysis is to identify opportunities and trends in research related to the Scaffolding method's impact on Computational Thinking skills. The bibliometric method was used with data collection of articles from 2016-2022 through Google Scholar using the Publish or Perish software, yielding 1,000 articles. The study results showed that 50 articles were published from 2016-2022. Visualizations in the analysis using VOSviewer can be seen in the form of network visualization, overlay visualization, and density visualization. The network visualization map is used to see the interrelationships and clusters of research themes based on keywords. Overlay visualization is used to identify the years when related research themes were conducted. Meanwhile, density visualization is used to analyze research themes that are saturated and those that are still rarely studied. Based on data analysis using VOSviewer, the research trend on Scaffolding dan Computational Thinking from 2016 to 2022 is relatively new and has rarely been conducted previously.